3.3k views
0 votes
Use the Distributive Property to rewrite each expression without parentheses.1. 6(x+3)2. 5(y-4)3. - 7(m-1)4. 9(3x + 2)5. -3(7 +3p)6. 1 (8x-10)

1 Answer

7 votes

The distributive property states:


a(b+c)=a\cdot b+a\cdot c

so:


\begin{gathered} 6(x+3)=6\cdot x+6\cdot3=6x+18 \\ 5(y-4)=5\cdot y-5\cdot4=5y-20 \\ -7(m-1)=-7\cdot m-7\cdot(-1)=-7m+7 \\ 9(3x+2)=9\cdot3x+9\cdot2=27x+18 \\ -3(7+3p)=-3\cdot7-3\cdot3p=-21-9p \\ 1(8x-10)=1\cdot8x+1\cdot10=8x-10 \end{gathered}

User Nooitaf
by
7.1k points